2018
DOI: 10.3892/mmr.2018.8978
|View full text |Cite
|
Sign up to set email alerts
|

miR‑24 regulates angiogenesis in gliomas

Abstract: Gliomas are one of the most common and most aggressive types of central nervous system tumor. Angiogenesis is an important basis for the growth of solid tumors, including gliomas, which is regulated by microRNAs (miRNAs). However, the mechanism remains unclear. Recently, it was demonstrated that miR‑24 was upregulated in gliomas, so the aim of the present study is to establish whether the dysregulation of miR‑24 in glioma cells promotes microvascular proliferation of endothelial cells (ECs), and to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Since most of the findings were obtained using exogenously expressed miRNAs, further studies are required to evaluate the translational potential of our results. Nonetheless, our findings are consistent with the observation of miR-24 expression in endothelial cells [42][43][44]87] and its roles as a regulator of various cerebrovascular phenomena, including angiogenesis in gliomas [88,89] and vasospasm following subarachnoid hemorrhage [90]. The study also has some strengths, including the fact that the 3 -UTR of Neuropilin-1 that is targeted by miR-24 is highly conserved among species, from primates to rodents.…”
Section: Discussionsupporting
confidence: 90%
“…Since most of the findings were obtained using exogenously expressed miRNAs, further studies are required to evaluate the translational potential of our results. Nonetheless, our findings are consistent with the observation of miR-24 expression in endothelial cells [42][43][44]87] and its roles as a regulator of various cerebrovascular phenomena, including angiogenesis in gliomas [88,89] and vasospasm following subarachnoid hemorrhage [90]. The study also has some strengths, including the fact that the 3 -UTR of Neuropilin-1 that is targeted by miR-24 is highly conserved among species, from primates to rodents.…”
Section: Discussionsupporting
confidence: 90%
“…Since most of the ndings were obtained using exogenously expressed miRNAs, further studies are required to evaluate the translational potential of our results. Nonetheless, our ndings are consistent with the observation of miR-24 expression in endothelial cells [42][43][44]87] and its roles as a regulator of various cerebrovascular phenomena, including angiogenesis in gliomas [88,89] and vasospasm following subarachnoid hemorrhage [90]. The study also has some strengths, including the fact that the 3′-UTR of Neuropilin-1 that is targeted by miR-24 is highly conserved among species, from primates to rodents.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, it has been found that the change of miR‐24 expression in fibroblasts could affect the aging and functional state of fibroblasts by modifying the activity of DNA topoisomerase I, 33 and also affect the proliferation activity of fibroblasts by regulating the expression of cell cycle regulatory genes 34 . In terms of the influence on angiogenesis, it has been revealed that miR‐24 could regulate the expression of VEGF and TGF‐β in HUVECs cells through the signal pathway of Akt and β‐Catenin, and then participate in angiogenesis 35 . In addition, another study found that the down‐regulation of miR‐24 expression in high glucose environment could affect the proliferation, migration, differentiation and angiogenesis of vascular endothelial cells by targeting the transcription factor PATZ1 36 .…”
Section: Discussionmentioning
confidence: 99%